2021
DOI: 10.1108/ijoem-05-2020-0495
|View full text |Cite
|
Sign up to set email alerts
|

Do innovations improve firm performance in the Indian manufacturing sector? A mediation and synergy effect analysis

Abstract: PurposeThis study examines the effects of both technological and non-technological innovations on the overall performance of Indian manufacturing firms, and identifies the mediation and synergy effects in the relationship between innovation and performance.Design/methodology/approachThe study applies the partial least squares structural equation modelling (PLS-SEM) technique using Smart PLS3 on a combined data set from the World Bank Enterprise Survey and the follow-up Innovation Survey for India in 2014. Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 94 publications
0
9
0
1
Order By: Relevance
“…Rosenbusch et al (2011) argued that the relationship between innovation and firm performance is context-specific and affected by several factors. Fatema and Islam (2021) found that technological innovations directly impact firm performance. In contrast, the effects of nontechnological innovations on firm performance are mediated by other factors.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Rosenbusch et al (2011) argued that the relationship between innovation and firm performance is context-specific and affected by several factors. Fatema and Islam (2021) found that technological innovations directly impact firm performance. In contrast, the effects of nontechnological innovations on firm performance are mediated by other factors.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…It also plays a critical role as an influential hub that transforms the positive effects of innovations into the different aspects of the firm’s performance. In a recent study, Fatema and Islam (2021) found that the effects of nontechnological innovations (marketing and organization innovation) on a firm’s performance are fully mediated by innovative performance.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations